A Low concentration hydrogen peroxide detection kit and the low concentration hydrogen peroxide detection method using the same - PARK JONG TAEK (2024)
The present invention provides a kit for detecting a low concentration hydrogen peroxide concentration and a method for detecting a low concentration hydrogen peroxide using the same, wherein the kit for detecting a low concentration hydrogen peroxide concentration has a simple measurement procedure, is economical with simple addition of chemicals, is accurate in measurement, and remarkably increases accuracy of measurement when measuring a low concentration hydrogen peroxide concentration to derive a reliable measurement result. The kit for detecting the low concentration of hydrogen peroxide of the present invention is formed by including a hydroquinone powder (a), an anilpermonic solution (b), and a molybdate solution (c). 본 발명은 검체수중의 미량의 과산화수소 농도를 측정하기 위한 검출키트에 관한 것으로, 구체적으로는 과산화수소(H2O2, Hydrogen peroxide)함유 시료수와 반응하여 발색하는 과산화수소 검출키트를 이용한 저농도 과산화수소 검출방법에 관한 것이다. 본 발명은 퀴논 파우더(Hydroquinone powder)(A), 아닐퍼닉 용액(B), 몰리브데이트 용액(C)이 포함되어 형성된 과산화수소 검출시약을 포함하는 저농도 과산화수소 농도 검출키트를 제공한다. 또한 본 발명은 상기한 퀴논 파우더(Hydroquinone powder)(A)는 하이드로퀴논 파우더이고, 상기한 아닐퍼닉 용액(B)은 아닐린 설페이트(Anilin sulfate)와 설포닐릭 애시드(Sulfanilic acid)를 증류수에 용해시킨 용액이며, 상기한 몰리브데이트 용액(C)은 소디움 몰리브데이트(Sodium Molybdate)와 설포닐릭 애시드(Sulfanilic acid)를 증류수에 용해시킨 용액인 것을 특징으로 하는 저농도 과산화수소 농도 검출키트를 제공한다. 또한 본 발명은 상기의 저농도의 과산화수소 농도 검출키트의 과산화수소 검출시약을 측정하고자 하는 과산화수소가 포함된 시료와 혼합하여 발색시키는 과정(1과정), 표준액에 대한 검량선을 작성하는 과정(2과정), 상기한 시료와 과산화수소 검출시약을 혼합하여 발색된 측정 시료를 측정용기에 넣어 시료에 포함된 과산화수소의 농도를 측정하는 과정(3과정)을 포함하는 저농도의 과산화수소 농도 측정 방법을 제공한다.